A NEW SOLUTION CONCEPT FOR SOLVING MULTIOBJECTIVE FRACTIONAL PROGRAMMING PROBLEM - Cevikel, Adem Cengiz (YILDIZ TECHNICAL UNIV, 2019)
In this work, we have proposed a solution to multiobjective fractional programming problems (MFPPs) by using the first-order Multiplicative Taylor expansion of these objective functions at optimal points of each fractional objective functions in feasible region. MFPP reduces to an equivalent Multiobjective Linear Programming Problem (MLPP). The resulting MLPP is solved assuming that weights of these linear objective functions are equal and considering the sum of the these linear objective functions. Thus, the problem is reduced to a single objective. The proposed solution to MFPP always yields efficient solution. Therefore, the complexity in solving MFPP has reduced easy computational and to show the efficiency of the Multiplicative Taylor series method, we applied the method to some problems.
Keywords: Fractional programming; multiobjective fractional programming; multiplicative derivation; Engineering